Keterkaitan Antara Managerial ownership, Capital Structure dan Investment Decision Dalam Perspektif Convergence – Interest hypothesis - Ningtias, Ika Ladyana; Ismiyanti, Fitri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the effect of managerial ownership, capital structure, and investment decisions in the convergence of perspective –interest hypothesis. This type of research is quantitative analytic. The data analysis method used regression for panel model 2 and model 3, as well as the simultaneous Equation model for model 1. This study used a statistical regression coefficient test (t-test) for bivariable analysis, F test, and R2 test. The results of the interpretation of model 1 and model 2 (without outliers) are not normally distributed, there is no multicollinearity, there are no symptoms of heteroscedasticity and there is a positive autocorrelation. The results of the interpretation of model 3 (without outliers) are normally distributed, there is no multicollinearity, there are symptoms of heteroscedasticity and there a positive autocorrelation The result for the study can be concluded classical assumption test show that the three models have abnormal symptoms and heteroscedasticity. The researcher has removed the data outliers one by one in the three models and transformed data into the third model. We suggest adding different variables such as dividend payout decisions. As well as being able to will add a sampling period that more samples are studied and consider taking samples from other companies for next research.